1012 Surgical Trainee Satisfaction Variations with Seniority and Region: An Evaluation of General Medical Council National Training Survey. (4th May 2021) - Fan, K S; McKenna, J; Chan, J
Abstract: Aim: The General Medical Council (GMC) National Training Survey invites all doctors in training and this study evaluates satisfaction in surgical training and variations with speciality, seniority, and training region. Method: All survey results were obtained from the GMC website. Responses of trainees, ranging from foundation training to registrar, were collected and categorised by speciality, training stage and location. Results: 9465 surgical trainees completed the study in 2019. The highest indicators were Educational Supervision (97.68), Clinical Supervision (87.42) and Clinical Supervision (out of hours) (87.28). The lowest were Workload (44.60), Rota Design (56.00) and Local Teaching (59.31). Highest and lowest ranking specialities were oral and maxillofacial surgery (84.25) and vascular surgery (73.95). Satisfaction varied significantly across training stages, with speciality trainees highest (82.58) overall and foundation year 1 lowest (70.03). London scored highest (77.95) and Northern Ireland, Scotland and Wales collectively scored 77.13. Within England, South England ranked highest in five specialities but only orthopaedics and neurosurgery showed significant national variations. Conclusions: Our data show variations in training satisfaction across many training cohorts. Satisfaction increases with surgeon seniority. Trainers and educational boards should target interventions to improve the quality of training for all grades of trainees and ensure appropriate curriculum coverage and address specific concerns.